PMO-070 FREKA® pexact placement in patients with head and neck cancer—the city hospital experience. (28th May 2012) - Disney, B R; Nizamuddin, M; Tanajura, A; Anderson, M; Lewis, M
Abstract : Introduction: Patients with head and neck cancer are at risk of malnutrition as a direct result of the tumour or as a result of treatment, that is, chemo-radiotherapy. Oral intake may not be enough to maintain nutrition, therefore many patients receive enteral feeding via a percutaneous endoscopic gastrostomy (PEG). A standard pull-through PEG may expose patients to the risk of tumour seeding within the tract in patients with oro-pharyngeal and oesophageal cancers. Current British Society of Gastroenterology guidelines recommend consideration for a direct gastric puncture technique and gastropexy for percutaneous feeding tube placement, with the technique being considered mandatory in those patients being treated with curative intent. The Freka ® Pexact (Fresenius Kabi, Germany) set was used in our setting. We aimed to review our practice of this technique with particular attention to safety and complication rates with this method of PEG insertion. Methods: Patients having a Freka ® Pexact placement for nutritional support at City Hospital, Birmingham, UK from 2009 to 2011 were identified using the ADAM ® medical documentation system (Fujinon Europe GmbH, Willich, Germany) and the Nutrition team logs. Complications, peristomal infection and 30-day mortality were documented after review of case notes and liaison with Community Nutrition Nurses. Results: A total of 30 patients having Freka ® Pexact placement were identified. The insertion was carried out as a day case procedure in 93.3% (n=28) of cases. Of these 76.7% were male (n=23). The mean age of patients was 58 years (range 35–81). All Freka ® Pexact (n=30) were inserted for nutritional support in patients with head and neck cancer. Prophylactic antibiotics were received by 83.3% (n=25). Success of Freka ® Pexact placement was 100% (n=30) with no immediate complications or procedure related mortality. Two patients (6.7%) were admitted for PEG related problems within 30 days. Peristomal infections occurred in 36.7% (n=11) of cases. The most common problem, other than infection, post-procedure was sutures becoming untied or falling out, this occurred in 16.6% (n=5) of patients, with consequence. There were no deaths at 30 days. Conclusion: Pexact insertion is safe and can be performed as a day case procedure. There are minimal complications. Our results compare favourably with those in the literature. This technique should be used in all patients having a PEG inserted for nutritional support in head and neck cancer. Competing interests: None declared.